Proposal of University Social Responsibility Chilean Case, Lessons to be Learned - Bustamante Sanchez, Yolanda (2019)
In the context of the existing social problems: poverty (hunger, diseases, insecurity, racism, and migration), pollution of the planet: air, water, soil, situations of violence in the community and other forms of degradation and social damage. The University must assume its responsibility as established by the Political Constitution of Peru, University Law 30220. International regulations established in the Global Compact Network that commit the adherence of institutions to compliance with its principles and guidelines of respect for Human Rights , Labor Rights, the Environment, ISO 26000, Standard SA8000, Social Accountability AA1000, the Global University Network for Innovation-GUNI (UNESCO-UNU-ACUP). The objective of this proposal is to determine the strategies for a successful University Social Responsibility (R.S.U.). Establish the importance of the media, Information, and Communication Technologies in achieving the R.S.U. And to recognize the value of institutional policies in the implementation of a socially responsible culture in the university context that will have a great impact on productivity, the satisfaction of human resources, the care and preservation of natural capital and the strengthening of institutional commitment.